A Novel Method to Evaluate the Reproductive Potential of Phymastichus coffea (Hymenoptera: Eulophidae) in Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae) Under Laboratory Conditions. Issue 6 (7th December 2018) - Portilla, Maribel; Grodowitz, Michael
Abstract: Life fertility tables were constructed for Phymastichus coffea LaSalle, the only known endoparasitoid wasp that attacks the adult female of the coffee berry borer (CBB) Hypothenemus hampei Ferrari. No preoviposition period was observed, and the parasitoid female attacked the CBB females immediately after emergence. The reproductive period was 20.33 (±0.87 SE) h and the postreproductive period of 14.78 (±0.99 SE) h. Mean generation time was 37 d. Median longevity for female and male fed on honey-water solution (50:50) was 35.22 (±1.18 SE) and 17.16 (±0.96 SE) h, respectively. The highest oviposition values were observed during the first 4 h after emergence. The sex ratio (F:M) was 1.11 (±0.31 SE): 1.04 (±0.32 SE) with a finite rate of increase [λ] of 1.06 (±0.002 SE) wasp per days and a r m value of 0.067 (±0.002 SE). Gross fecundity [ M x ] and net fecundity [ m x ] were 19.87 (±1.57 SE) males and females per female and 10.9 (±0.88 SE) females per female, respectively. The net reproductive rate [ R 0 ] was 9.49 (±0.75 SE) female per wasp. This study was designed to quantify reproductive rates of P. coffea in CBB females reared on artificial diets and used to improve a mass rearing system for this parasitoid.